Mechanismen der Auslösung hochreichender Konvektion im südwestdeutschen Mittelgebirgsraum - Mahlke, Holger Matthias (Wissenschaftliche Berichte des Instituts für Meteorologie und Klimaforschung des Karlsruher Instituts für Technologie, 2017)
The study discusses the occurrence of precipitation induced by deep convection in Germany's southwestern low mountain range in summer of 2007. Based on statistical methods and a case study, the mechanisms triggering the precipitation are described. The complex terrain proved to be a significant factor (divergent flow regimes), among others.